(untitled) (American Journal of Business Management, Economics and Banking, 2025)
In the article, at the current stage of the liberalization of the economy and the modernization of the tax system in the Republic of Uzbekistan, the advantages and unique features of the creative approach to effective measures to regulate and stimulate economic development through taxes are scientifically justified.